Pradhan Mantri Kisan Samman Nidhi (PM-KISAN) and the adoption of modern agricultural technologies in Uttar Pradesh, India - Varshney, Deepak; Joshi, Pramod Kumar; Roy, Devesh; Kumar, Anjani (International Food Policy Research Institute, 2020)
The Pradhan Mantri Kisan Samman Nidhi (PM-KISAN) scheme aims to provide income support to farmers to facilitate timely access to inputs by easing their liquidity needs. This study, based on 1,406 farmers of Uttar Pradesh and using a binary choice model, examines the scheme’s targeting accuracy and the correlates of farmers’ spending patterns. Triple difference with matching estimators are used to identify the differential impact of PM-KISAN on Krishi Vigyan Kendras (farm science centers, or KVKs) beneficiaries. Results show that PM-KISAN reached to one-third of all the farmers in the first three months of its implementation. Moreover, the study finds no selection bias based on social, economic and agricultural characteristics. The scheme has significantly helped those who are relatively more dependent on agriculture and have poor access to credit. Moreover, scheme has significantly stimulated the KVK ’s impact on the adoption of modern cultivars.